Program Asistensi Mengajar Sebagai Upaya Peningkatan Motivasi Belajar Peserta Didik SMP Negeri 12 Kota bima dan SDN 64 Soribaru - Nadilah Nadilah; Alwi Alwi; M. Rimawan; HidratulIftar HidratulIftar; Uswatun Hasanah (Fakultas Teknik Universitas Cenderawasih, 2024)
The teaching assistance program is one of the main work programs in KKNT-MBKM which provides students with the opportunity to study outside the campus environment. This activity is carried out for 1 week and takes place at SDN 64 Sori Baru and SMPN 12 Kota Bima, Lelamase Village, Bima City. In this Merdeka curriculum, students assist teachers in teaching and guiding students in understanding the subjects that will be taught at the school. In addition to these responsibilities, students must maintain a strong sense of morality and strive to increase students' enthusiasm for learning. Through this activity, it is hoped that students can improve their soft skills and work skills. As for schools, this activity is able to improve educational services and students gain understanding and knowledge in terms of learning, this work program has a major impact on the parties involved